The gate and temple of Ḫaldi in Ašotakert/Yeşılalıç and the evolution of Urartian cultic complexes - Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
This article presents a re-evaluation of an important Urartian archaeological site called Ašotakert/Yeşılalıç, located in eastern Turkey. The site is notable for its religious building, which is important for comprehending the evolution of Urartian religious architecture. This paper is divided into two parts, the first devoted to an assessment of the archaeological site of Yeşılalıç, and the second an attempt to explain the religious buildings identified there in terms of the Urartian religious architectural tradition, of which the main stages of development are outlined.